Sport science services to young football player and coaches - Peltola, E. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Aspire, Academy for Sports Excellence is a new concept in Qatar and in the Middle- East. Aspire was established in 2004. It is a sports school with elite sports programs including football. Aspire has excellent facilities and professional staff for modern sports/ football training. Aspire program is a junior preparation program with holistic service support. The goal in Aspire Academy is to create "optimal junior development program" to lay a solid foundation for young athletes to be future champions and professional players. Sport Science and Medicine support is integral part of the preparation of young players in Aspire. Each scientific discipline works closely with players and coaches. The support delivery is through service team model, where service team works closely with the coach of each team in a holistic manner. The staff in those squad/ team based service teams work closely and daily together regardless of their sport science expertise. In physiology and biomechanics the major sport science support is in four main categories: 1. Laboratory testing, 2. Sport specific field testing, 3. Match/ Competition analysis and training monitoring and 4. Applied research Laboratory testing and sport specific field testing is implemented in a systematic fashion in accordance with agreements negotiated with Head Coaches. Certain tests are uniform with all Aspire student athletes to collect long term information about the development of young athletes. As maturation and growth is an important factor when evaluating young athletes, maturation is assessed regularly with anthropometric measurements. For the first two sport science support categories there are clear testing protocols for everyone to follow. Match/ Competition analysis and training monitoring are integral part of servicing during daily training in Aspire and during training camps. Because of the hot weather and lack of regional competition, training camps are important part of the Aspire program. In most of Aspire sports the main junior competition takes place in Europe (football, athletics, squash). All testing, match/ competition analysis and training monitoring is done in close cooperation with coaches. Three times a year there is a comprehensive screening process including medical, physiotherapy, nutritional, psychological, anthropometric and physical qualities. Significant time is allocated for comprehensive holistic feedback and discussion with coaches about the results and their implications on training. Applied research will focus on topics related to the preparation of young athlete, maturation of young athlete, young athletes in hot environment, match analysis and long term development of young players. The applied research always supplements main servicing tasks.